Enhancing Upper Secondary Students’ Situational Engagement and Cognitive Prerequisites of Learning Through the Physically Active Academic Lessons Intervention: Protocol for a Mixed Methods Cluster Randomized Individual Crossover Trial - Syväoja, Heidi J.; Takalo, Susanna; Kukko, Tuomas; Salmela, Nina; Hakonen, Harto; Kulmala, Janne; Lindfors, Heidi; Oksanen, Hermanni; Räsänen, Pekka; Mäkitalo, Kati; Tammelin, Tuija H. (JMIR Publications Inc., 2026)
Background
Internationally, physical activity is successfully integrated into academic lessons in primary schools, showing promising results on cognition and student engagement. However, there is a lack of knowledge about its effects and feasibility for individual situated learning processes in upper secondary school.
Objective
This protocol describes the design and methods of the Physically Active Academic Lessons (PAAL) study, a mixed methods, cluster randomized, individual crossover trial. The PAAL study aims to examine the acute effects of physically active academic lessons on cognitive prerequisites of learning (alertness and executive functions) and situational engagement (behavioral, cognitive, and emotional engagement; disaffection; competence experiences; and help seeking), as well as factors modifying these effects (physical and mental load and perceived physical and academic competence). Further, subject teachers’ and students’ experiences and perceptions of physically active academic lessons in general upper secondary school will be explored.
Methods
The first part of the PAAL study involves exploring subject teachers’ experiences of facilitators, barriers, usefulness, and the meaning of physically active academic lessons for the situational learning process through semistructured interviews with 14 teachers. The second part consists of a cluster‑randomized individual crossover trial including 168 students in mathematics and foreign language lessons, followed by interviews with 30 students.
Results
Funding for the study was obtained in May 2023. Ethical approval for the teacher interviews was granted in September 2023, and for the student trial in December 2023. Data collection was completed between October 2023 and November 2024. Data analysis is ongoing. The findings of the study will provide essential evidence-based information on physically active classroom practices that support teachers and schools in implementing pedagogical methods that enhance student learning and well-being in upper secondary schools.
Conclusions
The background, design, content of the intervention, and methods of the PAAL study are presented. This study aims to address a gap in the literature regarding the feasibility and effectiveness of physically active methods during academic lessons in upper secondary school.